Impact of hyperhydration on the mortality risk in critically ill patients admitted in intensive care units: comparison between bioelectrical impedance vector analysis and cumulative fluid balance recording. Issue 1 (December 2016) - Samoni, Sara; Vigo, Valentina; Bonilla Reséndiz, Luis; Villa, Gianluca; De Rosa, Silvia; Nalesso, Federico; Ferrari, Fiorenza; Meola, Mario; Brendolan, Alessandra; Malacarne, Paolo; Forfori, Francesco; Bonato, Raffaele; et al.
Abstract Background Studies have demonstrated a positive correlation between fluid overload (FO) and adverse outcomes in critically ill patients. The present study aims at defining the impact of hyperhydration on the Intensive Care Unit (ICU) mortality risk, comparing Bioelectrical Impedance Vector Analysis (BIVA) assessment with cumulative fluid balance (CFB) recording. Methods We performed a prospective, dual-centre, clinician-blinded, observational study of consecutive patients admitted to ICU with an expected length of ICU stay of at least 72 hours. During observational period (72–120 hours), CFB was recorded and cumulative FO was calculated. At the admission and daily during the observational period, BIVA was performed. We considered FO between 5 % and 9.99 % as moderate and a FO ≥10 % as severe. According to BIVA hydration scale of lean body mass, patients were classified as normohydrated (>72.7 %–74.3 %), mild (>71 %–72.7 %), moderate (>69 %–71 %) and severe (≤69 %) dehydrated and mild (>74.3 %–81 %), moderate (>81 %–87 %) and severe (>87 %) hyperhydrated. Two multivariate logistic regression models were performed: the ICU mortality was the response variable, while the predictor variables were hyperhydration, measured by BIVA (BIVA model), and FO (FO model). Ap -value <0.05 was considered to indicate statistical significance. Results One hundred and twenty-five patients were enrolled (mean age 64.8 ± 16.0 years, 65.6 % male). Five hundred and fifteen BIVA measurements were performed. The mean CFB recorded at the end of the observational period was 2.7 ± 4.1 L, while the maximum hydration of lean body mass estimated by BIVA was 83.67 ± 6.39 %. Severe hyperhydration measured by BIVA was the only variable found to be significantly associated with ICU mortality (OR 22.91; 95 % CI 2.38–220.07;p  < 0.01). Conclusions The hydration status measured by BIVA seems to predict mortality risk in ICU patients better than the conventional method of fluid balance recording. Moreover, it appears to be safe, easy to use and adequate for bedside evaluation. Randomized clinical trials with an adequate sample size are needed to validate the diagnostic properties of BIVA in the goal-directed fluid management of critically ill patients in ICU.